Synthesis and characterization of water-based poly(vinyl acetate-co-butyl acrylate) latexes containing oligomeric protective colloid - Berber, Hale; Sarac, Ayfer; Yildirim, Huseyin (SPRINGER, 2011)
Poly(vinyl acetate-co-butyl acrylate) latexes having oligomeric N-methylol acrylamide were prepared by semi-continuous emulsion polymerization. The effects of new protective colloid and comonomer ratios on the physicochemical and colloidal properties of latexes were investigated. The changes in homopolymer and copolymer latexes were determined by measuring viscosity, particle size, molecular weight (MW), molecular weight distribution (MWD), and surface tension. (M) over bar (n) values of copolymer latexes were found to be lower than the MWs of the poly(vinyl acetate) and poly(butyl acrylate) homopolymers. In general, (M) over bar (n) and (M) over bar (w) values of copolymer latexes changed irregularly with increasing BuA ratio in the copolymer composition.
Keywords: Emulsion polymerization; Water-based latex; Copolymer; Stabilization; N-methylol acrylamide; Molecular weight distribution; VINYL-ACETATE; NONIONIC EMULSIFIERS; ETHOXYLATION DEGREE; COPOLYMERIZATION; BATCH; Polymer Science